2023
DOI: 10.1097/ijg.0000000000002209
|View full text |Cite
|
Sign up to set email alerts
|

Zonule-Associated Gene Variants in Isolated Ectopia Lentis and Glaucoma

Abstract: We report 3 novel variants in fibrillin-1 (FBN1) and latent transforming growth factor-β-binding protein 2 (LTBP2) in 3 families with isolated ectopia lentis (EL), which shed new light on the diagnosis and genetic counseling of EL and secondary glaucoma in clinical settings.Purpose: To explore the genetic mechanism in 3 families with isolated EL and secondary angle closure glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Another recent study found an increased expression of LTBP1 in the keratotomy wounds of mouse corneas [ 67 ]. LTBP2 dysregulation has been linked to eye diseases in numerous studies, including glaucoma [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Two studies reported LTBP1 and LTBP2 upregulation in the anterior segment of human tissues with pseudoexfoliation syndrome [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found an increased expression of LTBP1 in the keratotomy wounds of mouse corneas [ 67 ]. LTBP2 dysregulation has been linked to eye diseases in numerous studies, including glaucoma [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Two studies reported LTBP1 and LTBP2 upregulation in the anterior segment of human tissues with pseudoexfoliation syndrome [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%